Impacts of professional development focused on teaching engineering applications of mathematics and science. (26th October 2020) - Hammack, Rebekah; Gannon, Paul; Foreman, Christine; Meyer, Elijah
Abstract: With the recent national emphasis on preparing children for future careers in science, technology, engineering, and mathematics, K‐12 teachers are being called upon to include engineering in their instruction. This study explores the impacts of a summer professional development (PD) program focused on the engineering applications of mathematics and science on in‐service K‐12 teachers' (a) personal engineering efficacy, (b) engineering teaching efficacy, and (c) perceived barriers to teaching engineering. This quantitative study revealed that a single engineering‐focused PD could increase teachers' personal engineering efficacy and engineering teaching efficacy and reduce particular perceived barriers to teaching engineering. No differences existed in pre‐ to post workshop assessment scores based on grade level taught, gender, or years of teaching experiences. However, pre‐ to post workshop assessment differences existed between participants depending on the discipline they taught and wether or not they had previously used engineering activities in their classrooms. These findings suggest that a single engineering PD can have significant impacts on in‐service teachers' personal engineering efficacy, engineering teaching efficacy, and perceived barriers to teaching engineering, but a one‐size‐fits‐all approach to such PD is not equally effective for all participants.